Influence of paclobutrazol on growth, yield and quality of mango (Bangladesh Journal of Agricultural Research, 2018)
A study on the effect of paclobutrazol on vegetative growth, harvest time, yield and quality of mango cv. BARI Mango-3 (Amrapali) was conducted at the Germplasm Centre, Department of Horticulture, Bangladesh Agricultural University, Mymensingh. Paclobutrazol @ 7500 ppm, 10000 ppm and control (water application) along with two application times; 15 July and 15 October were used with three replications following RCBD design. Paclobutrazol soil drenched @ 7500 ppm or 10000 ppm on 15 July distinctly advanced panicle emergence and fruit harvest by 23 and 22 days, respectively. Application of paclobutrazol @ 7500 ppm on 15 July produced the highest number of fruits (185) as well as yield (55.05 kg) per plant and the biggest fruit (303.67 g). Paclobutrazol @ 7500 ppm applied on 15 July or 15 October also resulted in higher edible portion, lower stone pulp ratio, longer shelf life, higher TSS, increased vitamin C, lower titratable acidity, higher dry matter, reducing, non-reducing and total sugar contents.Bangladesh J. Agril. Res. 43(1): 1-12, March 2018